A Novel Noncontact Diffuse Correlation Spectroscopy Device for Assessing Blood Flow in Mastectomy Skin Flaps: A Prospective Study in Patients Undergoing Prosthesis-Based Reconstruction. Issue 1 (July 2017) - Agochukwu, Nneamaka B.; Huang, Chong; Zhao, Mingjun; Bahrani, Ahmed A.; Chen, Li; McGrath, Patrick; Yu, Guoqiang; Wong, Lesley
Abstract : Summary: A new advanced technology, noncontact diffuse correlation spectroscopy, has been recently developed for the measurement of tissue blood flow through analyzing the motions of red blood cells in deep tissues. This technology is portable, inexpensive, and noninvasive, and can measure up to 1.5-cm tissue depth. In this prospective study, the authors aimed to explore the use of this novel device in the prediction of mastectomy skin flap necrosis. The noncontact diffuse correlation spectroscopy device was used to measure mastectomy skin flap flow in patients undergoing mastectomy and immediate implant-based breast reconstruction before and immediately after mastectomy, and after placement of the prosthesis. Patients were tracked for the development of complications, including skin necrosis and the need for further surgery. Nineteen patients were enrolled in the study. Four patients (21 percent) developed skin necrosis, one of which required additional surgery. The difference in relative blood flow levels immediately after mastectomy in patients with or without necrosis was statistically significant, with values of 0.27 ± 0.11 and 0.66 ± 0.22, respectively ( p = 0.0005). Relative blood flow measurements immediately after mastectomy show a significant high accuracy in prediction of skin flap necrosis, with an area under the receiver operating characteristic curve of 0.95 (95 percent confidence interval, 0.81 to 1). The noncontact diffuse correlation spectroscopy device is a promising tool that provides objective information regarding mastectomy skin flap viability intraoperatively, allowing surgeons early identification of those compromised and ischemic flaps with the hope of potentially salvaging them. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV. Abstract : Supplemental Digital Content is available in the text.